2016
DOI: 10.1140/epjb/e2016-60331-5
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagrams of bosonic ABn chains

Abstract: Abstract. The ABN−1 chain is a system that consists of repeating a unit cell with N sites, where between the A and B sites there is an energy difference of λ. We considered bosons in these special lattices and took into account the kinetic energy, the local two-body interaction, and the inhomogenous local energy in the Hamiltonian. We found the charge density wave (CDW) and superfluid and Mott insulator phases, and constructed the phase diagram for N = 2 and 3 at the thermodynamic limit. The system exhibited i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In conclusion, the superlattice potential leads to the emergence of diverse CDW insulator phases for semi-integer and integer densities and drives quantum phase transitions between insulator phases (Mott or CDW) and superfluid ones for particular values of the parameters. The above results and phase diagrams have previously been obtained by some authors, using diverse numerical methods [35][36][37]40]. The effective description of spinor bosons provides a local spin-dependent interaction term, whose effect on the ground state of spinor bosons in an AB chain we want to study.…”
Section: Numerical Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…In conclusion, the superlattice potential leads to the emergence of diverse CDW insulator phases for semi-integer and integer densities and drives quantum phase transitions between insulator phases (Mott or CDW) and superfluid ones for particular values of the parameters. The above results and phase diagrams have previously been obtained by some authors, using diverse numerical methods [35][36][37]40]. The effective description of spinor bosons provides a local spin-dependent interaction term, whose effect on the ground state of spinor bosons in an AB chain we want to study.…”
Section: Numerical Resultsmentioning
confidence: 83%
“…Spinless bosons in non-homogeneous lattices have been considered by several authors, using diverse analytical and numerical methods [30][31][32][33][34][35][36][37][38][39][40]. From a general point * jsilvav@unal.edu.co of view, these studies found that the ground state can be diverse, as a function of the parameters; for instance, charge density wave (CDW), Mott insulator, superfluid or "Bose glass" phases have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation